Aplastic anemia secondary to tyrosine kinase inhibitor therapy in a patient with chronic myeloid leukemia. (March 2022) - Kassar, Olfa; Mallek, Rahma; Ben Said, Fatma; Kallel, Faten; Ksouda, Kamilia; Khabir, Abdelmajid; Elloumi, Moez
Introduction: Nilotinib, as the second generation of tyrosine kinase inhibitor, has significant efficacy in patients with chronic myeloid leukemia resistant or intolerant to Imatinib. Aplastic anemia induced by tyrosine kinase inhibitors is an uncommon complication. Case report: A 34-year-old female case with CML in the chronic phase was treated with Imatinib in first-line therapy. Nilotinib was switched because of failure to achieve complete cytogenetic response at 6 months following Imatinib. Three years with Nilotinib, the patient developed a persistent pancytopenia grade 4 while a major molecular response was achieved. Management & Outcome: Nilotinib was discontinued. However, the hematologic finding of the patient had not recovered after three months. A bone marrow biopsy showed marked hypocellularity and fatty tissue without evidence of myelofibrosis. Immunosuppressive therapy was started. Unfortunately, the patient died due to septic and hemorrhagic shock nine months after Nilotinib interruption. According to Naranjo's algorithm, the causality relationship with the drug is probable with a score of 5. Discussion: Aplastic anemia is an uncommon adverse event of tyrosine kinase inhibitors but it can be a fatal complication. The early diagnosis of aplastic anemia related to Nilotinib therapy is needed to avoid further detrimental effects of the drug.